한의 진료 지원 모바일 애플리케이션 - 김상균(Sang Kyun Kim); 오용택(Yong Taek Oh); 김안나(An Na Kim); 김지영(Ji Young Kim); 예상준(Sang Jun Yea); 김철(Chul Kim); 장현철(Hyun Chul Jang) (동의생리병리학회지, 2012)
We in this paper propose a mobile application for supporting medical treatment based on Korean medicine ontology. It has three processes for treating patients. First, after a pattern is decided for patient' symptoms, a formula for the pattern is selected and medicinal materials constituting the formula is added or removed. Second, formulas are searched and prescribed for patient's symptoms without the process of the pattern decision. Third, after medicinal materials are searched for patient's symptoms, formulas consisting of the medicinal materials are prescribed. Our application aims to help korean medicine doctors treat patients through providing decision supporting functions such as the recommendation of symptoms of diseases accompanying patient's symptom. Doctors generally diagnosis patients according to their experiences and knowledges. Nevertheless, our application can help them, providing diverse forms of information that they may miss in the medical treatment.